In Vitro Studies on the Adhesion of Fibrobacter Succinogenes Strain D3 to Macrocrystalline Cellulose - Sieo, Chin Chin (1997)
In the present study, the factors affecting adhesion of Fibrobacter succinogenes strain D3 to microcrystalline cellulose avicel were investigated. Fibrobacter succinogenes showed the highest percentage of adhesion (85%) during late exponential phase of growth. During lag phase, 50 - 55% of the bacterial cells were adherent and during death phase, 60 - 70% of the cells were adherent. Adhesion of bacterial cells to avicel was significantly (P<0.05) affected by pH and temperature and significant (P<0.05) interaction between these two factors was also observed. The optimum pH for cell adhesion was 6.5 and the optimum temperature was 39°C. At pH 6 . 5 , the adhering ability of the cells was reduced when the temperature was raised to 5 0°C and 60°C or lowered to 4°C and 22°C. At this pH, the effect of temperature on adhesion was greater at high temperature than at low temperature. At 50°C and 60°C, only 20 - 27% adhesion was observed but at 4°C and 22°C, 48 - 5 8% adhesion was obtained. At other combinations of condition (PH 4.0, 5.6, 7.0, 8.0 and temperature 4, 22, 39, 5 0, 60°C), less than 20% adhesion was observed. The adhering ability of the bacterial cells was also reduced after the cells were treated with proteolytic enzymes such as thermolysin and pronase. Lipase and dextranase did not affect the adhesion of the cells. The study usmg scannmg electron microscopy and transmission electron microscopy showed that the adhesion of F. succinogenes was first mediated by fine structures radiating from the outer layer of the cell and then by the glycocalyx. Initial adhesion by these fine structures was observed after 1 0 min of incubation with avicel. After 1 8 h of incubation, the bacteria had digested away the cellulose at the point of contact and penetrated into the substrate. Pits of digestion surrounding the bacteria were particularly evident after 30 h of incubation and larger digestion pits were observed after 56 h of incubation. Studies were also carried out to detect the cellulose-binding proteins (CBPs) of the cells. In this study, Buffer A supplemented with 1% (w/v) carboxymethylcellulose (CMC), 1 0% (w/v) cellobiose or 5% (w/v) sodium dodecyl sulphate (SDS) were used to elute CBPs from avicel incubated with cell lysate of F. succinogenes. Buffer A supplemented with CMC was found to elute two maj or proteins ( 1 20 kDa and 1 00 kDa) and a few minor proteins ranging from 35 kDa to 60 kDa. Buffer A supplemented with cellobiose or SDS eluted proteins with approximate weights of 240, 1 20 and 1 00 kDa. These three CBPs (240, 1 20 and 1 00 kDa) were involved in the adhesion process of the cells as cells with reduced adhering ability after being treated with proteolytic enzymes such as thermo lysin and pronase did not show these CBPs. Other than possessing the ability to bind, the 240 kDa CBP showed xylanase activity and the 1 20 kDa protein showed carboxymethylcellulase (CMCase) activity in the cell lysate. The 1 00 kDa CBP did not show any of the two enzyme activities shown by 240 kDa and 1 2 0 kDa CBPs